Development of Discovery Learning-Based Learning Devices To Improve Mathematical Problem Solving Abilities - PS, Muktabar Annurul; Yerizon, Yerizon (Jurnal Perspektif, 2025)
This research is a development research that uses the Plomp model. The initial research consists of needs analysis, curriculum analysis, concept analysis, and student characteristics analysis. The development or prototyping process consists of individual evaluation, small group evaluation, and expert evaluation. In addition, the evaluation stage consists of effectiveness testing that tests mathematical problem solving ability. The results showed that the teaching module validation provided by mathematics lecturers received an average score of 3.75 very valid for teaching module validation aspects. Based on the practicality test of the teaching module conducted by a teacher and students, it shows that the teaching module gets an average score of 88.81% or very practical criteria with 89.58% teacher and 88.05% student responses and based on the effectiveness test by giving mathematical problem solving questions, 90% of students meet the completeness, indicating that the mathematics teaching module is very valid, practical, and effective in improving students' mathematical problem solving skills at SMP Negeri 1 Tapanuli Tengah. The recommendations and suggestions from this research are expected to help teachers in using the independent curriculum for teaching and learning activities to choose the right learning model to trigger students' enthusiasm and learning activities, such as the application of the Discovery Learning model which can create a passionate learning atmosphere.